TEACHING HORTATORY EXPOSITION TEXT THROUGH CLUSTERING TECHNIQUE - Amri, Samsul (Universitas Wiralodra, 2018)
Having writing problems was faced by students. This research purposed to describe the teaching process how Clustering Technique improves the students' writing skill of hortatory exposition text, and what influenced factors of their writing improvement. This is a Classroom Action Research. The participants of the research were the students of grade XI AB-3 of MA Darul Hikmah Pekanbaru. The data were collected in each cycle from observation checklists, field notes, interviews, and writing tests. Then the researcher found that Clustering Technique enables to improve better the students' writing skill of hortatory exposition text through the process of socializing, reviewing, controlling, monitoring, assisting, motivating, and practicing. Consequently, the students could improve their writing skill which involved the mean score improvement of writing indicators; grammar, vocabulary, mechanics, fluency, and organization. It could be seen from the improvement of the base score mean score (56.32), post-test I (64.23), and posttest II (73.85). Furthermore, the factors that influenced the improvement of their writing skill involved creative thinking, students' motivation, amount of writing practices, students' prior knowledge, and the teacher's role. To sum up, the implementation of Clustering Technique in teaching writing of hortatory exposition text could provide positive results on their writing skill.